Ecological Crisis and Human Security: A Legal Analysis of the Exploitation of the Sei Ular River - Triono Eddy; Agustina Agustina; Sagita Purnomo (Khazanah Hukum, 2025)
River empowerment for tourism and sustainable agriculture has a positive impact on environmental sustainability and community welfare. However, these positive benefits have not been fully felt by the community in Sei Ular River, North Sumatra. Increasingly rampant illegal mining activities have deprived the community of their social rights, especially for a good and healthy environment. Government policies and existing legal instruments have not been optimal in solving the problem due to inconsistencies in law enforcement, lack of coordination between authorities, and low public awareness to protect river ecosystems. The research conducted is normative juridical, namely analyzing written law, jurisprudence, and norms that live in society. The descriptive-analytical approach aims to retrieve data systematically, factually, and accurately on a problem based on applicable laws and legal norms. The results of this study indicate that regulations and legal protection for the community due to illegal mining in Sei Ular River have been regulated starting from laws, government regulations, to regional regulations, but these legal instruments have not been effective enough in protecting the community from the impact of illegal mining activities, as a result, there have been violations of fundamental rights that affect community welfare. Empowerment of the Sei Ular River for tourism and sustainable agriculture and its concrete benefits, namely, involving the community in the management of tourist destinations in the river area, building dams and irrigation channels for farmers, socialization, strict action (sanctions) against illegal mining actors, actively collaborating with various parties in conducting surveillance to protect the Sei Ular River ecosystem. In addition, the government also requires illegal mining actors who pollute the Sei Ular River to compensate affected communities and restore the environmental damage caused.